Gereja Profetik Menurut Paulo Freire - Merensiana Hale; Franklin Ton (Institut Agama Kristen Negeri Toraja, 2021)
This paper aims to elaborate Paulo Freire's thoughts on the prophetic church and its relevance for the church today. The method used to achieve the goal is library research. In particular, it is focused on the thoughts of one educational figure, Paulo Freire, who contributed to his thoughts on liberation education by the church in the prophetic church concept. The conclusion of this paper is that education in the church is an important means of bringing about change in society. Consientization by the church is carried out in the spirit of raising the critical awareness of the congregation. Abstrak Tulisan ini bertujuan untuk mengelaborasi pemikiran Paulo Freire tentang gereja yang profetik dan relevansinya bagi gereja masa kini. Metode yang digunakan untuk mencapai tujuan adalah penelitian kepustakaan (library research). Secara khusus difokuskan pada pemikiran salah satu tokoh pendidikan, Paulo Freire, yang memberi sumbangan pemikiran mengenai pendidikan pembebasan oleh gereja dalam konsep gereja yang profetik. Kesimpulan tulisan ini adalah pendidikan dalam gereja merupakan sarana penting dalam mewujudkan perubahan dalam masyarakat. Konsientisasi oleh gereja dilakukan dengan semangat menumbuhkan kesadaran kritis jemaat.